Augmented reality for non-destructive testing imaging - Pang, Jia Jie (2019)
Non-destructive testing (NDT) is an identification and characterization method to analysis and evaluate the condition or examine the physical properties of a material or structure without the need to physically remove any material or break its components down. NDT has been growing in popularity and technological advancement as with the increasing reliance on technology and expansion of engineering to meet this demand. Thus, there is a need to ensure the reliability and safety of these complex engineering constructs. Especially in areas like construction and aerospace, failure to spot and rectify any defects within the material (e.g. internal crack within the aircraft wing) can result in catastrophic outcomes [1]. To obtain accurate and reliable data, most NDT techniques require a good surface contact between the testing surface and sensor and depending on the method, there are difference in the evaluation of the composites and applications in testing. For the purpose of this study, the contact method of ultrasonic testing will be used to evaluate and identify any defects or cracks within the composite [2]. Augmented reality uses the real world to generate Three-dimensional (3D) images or objects that users can see in the real world using special glasses/goggles. Augmented reality is bounded by the law of physics which is the balance between the real and virtual environment also known as mixed reality [3]. Conventionally, NDT methods are viewed using a computer screen attached to measuring instruments. However, these results are not only inconvenience for the user but gives a poor representation of the defect as the user must use his/her own deduction and spatial awareness which may varies from person to person. Therefore, the purpose of this study is to create and develop an augmented reality software simulation so that users can see the defect by overlaying the ultrasonic image to have a better understanding and visual representation of the defect within the material or component. This simulation will be programmed within the augmented reality goggles so that users will be able to use NDT instruments to scan and simultaneously through the augmented reality software see the projected defect.